Development and implementation of a novel measure for quantifying training loads in rowing: The T2minute method - Tran, J.; Rice, A. J.; Main, L. C.; Gastin, P. B. (The Journal of Strength and Conditioning Research, 2014)
The systematic management of training requires accurate training load measurement. However, quantifying the training of elite Australian rowers is challenging because of (a) the multicenter, multistate structure of the national program; (b) the variety of training undertaken; and (c) the limitations of existing methods for quantifying the loads accumulated from varied training formats. Therefore, the purpose of this project was to develop a new measure for quantifying training loads in rowing (the T2minute method). Sport scientists and senior coaches at the National Rowing Center of Excellence collaborated to develop the measure, which incorporates training duration, intensity, and mode to quantify a single index of training load. To account for training at different intensities, the method uses standardized intensity zones (T zones) established at the Australian Institute of Sport. Each zone was assigned a weighting factor according to the curvilinear relationship between power output and blood lactate response. Each training mode was assigned a weighting factor based on whether coaches perceived it to be "harder" or "easier" than on-water rowing. A common measurement unit, the T2minute, was defined to normalize sessions in different modes to a single index of load; one T2minute is equivalent to 1 minute of on-water single scull rowing at T2 intensity (approximately 60-72% VO2max). The T2minute method was successfully implemented to support national training strategies in Australian high performance rowing. By incorporating duration, intensity, and mode, the T2minute method extends the concepts that underpin current load measures, providing 1 consistent system to quantify loads from varied training formats.